2022
DOI: 10.1007/s10899-021-10097-0
|View full text |Cite
|
Sign up to set email alerts
|

Using “Markers of Harm” to Track Risky Gambling in Two Cohorts of Online Sports Bettors

Abstract: Using "Markers of Harm" to Track Risky Gambling in Two Cohorts of Online Sports BettorsPlease note that this is a non-peer-reviewed pre-print that is currently under review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The high percentage of problem gamblers in self-report studies is in stark contrast to previous studies classifying problem gamblers using pure behavioral tracking data. McAuliffe et al ( 2022 ) reported that less than 1% of players were regarded as high-risk based on the Senet Group’s markers of harm. They also reported that Entain , which was part of the group of companies which defined the markers of harm, identified less than 6% of players as being high risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high percentage of problem gamblers in self-report studies is in stark contrast to previous studies classifying problem gamblers using pure behavioral tracking data. McAuliffe et al ( 2022 ) reported that less than 1% of players were regarded as high-risk based on the Senet Group’s markers of harm. They also reported that Entain , which was part of the group of companies which defined the markers of harm, identified less than 6% of players as being high risk.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a number of meetings between five major gambling operators – 888 Holdings, GVC Holdings (now called Entain ), Sky Betting & Gaming, William Hill , and Paddy Power – the Senet Group developed a set of nine markers of harm to identify problematic gambling (McAuliffe et al, 2022 ). The Senet Group is an organization which was established in 2014 by the leading high-street bookmakers in the UK which was then taken over by the Betting and Gaming Council (Narayan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, we deemed 44 records as potentially eligible for inclusion. From these, we excluded 26 for not meeting the eligibility criteria: 17 were not sufficiently related to the gambling field (e.g., Kim & Werbach, 2016;Uusitalo et al, 2021), 7 lacked a discussion of risks and/or ethical concerns (e.g., Auer & Griffiths, 2023;McAuliffe et al, 2022), and 4 were unidentified duplicates. We selected 16 studies to include in the final review.…”
Section: Resultsmentioning
confidence: 99%
“…In other work, a consortium of gambling operators developed the Markers of Harm system (i.e., an algorithm) to identify problematic sports-betting behaviors. Although some markers were positively associated with gambling engagement and proxies of problem gambling, researchers suggested that further adjustments should be made to improve the algorithm's group classification and risk thresholds ( McAuliffe, Louderback, Edson, LaPlante, & Nelson, 2022 ). Table 5 summarizes these studies.…”
Section: Resultsmentioning
confidence: 99%